Zinc transport in rice how to balance optimal plant requirements and human nutrition - Huang, Sheng (Journal of experimental botany, 2022)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.